CORRELATION OF SERUM FERRITIN WITH HAEMOGLOBIN A2 LEVEL IN BETA THALASSEMIA TRAITS - Hameed, Mehreen; Raziq, Fazle; Mir, Awal (Journal of Ayub Medical College Abbottabad, 2020)
Background: Haemoglobin-A2 is considered as a paramount diagnostic parameter for the detection of beta-thalassemia trait which may vary with the fluctuation of body iron stores. The current study aims to evaluate the correlation of serum ferritin as a parameter of body iron stores with haemoglobin-A2 level in beta-thalassemia traits. Methods: This cross-sectional study was conducted on total 134 known beta-thalassemia traits in Rehman Medical Institute-Peshawar, Pakistan from October 2018 to June 2019. Blood samples from the contributors were drawn in EDTA and plain tubes for complete blood counts, haemoglobin-A2 and serum ferritin estimation. Participants were categorized into 3 groups on the basis of iron status; beta-thalassemia traits with low ferritin (Group A), normal ferritin (Group B) and high ferritin levels (Group C). Pearson correlation was applied to analyse the correlation between the variables. Results: Out of total 134 known beta-thalassemia traits, 73 (54.5 %) were males and 61 (45.5%) were females. Participants of group A with low ferritin were 22 (16.4%), group B with normal ferritin were 96 (71.6%) and group C with high ferritin were 16 (11.9%). Group A shows lowest mean haemoglobin-A2 level comparatively to Group B and Group C, with some effect of serum ferritin on haemoglobin-A2 level. Conclusion: Haemoglobin-A2 value decreases when there is a decrease in serum ferritin and show slightly increase with high ferritin level as compared to normal ferritin level or body iron stores in beta-thalassemia traits. However, this correlation is not significant enough to mask the actual diagnosis of the disease. Keywords: Beta Thalassemia Trait; Haemoglobin A2 level; Serum Ferritin